Comparison of eight published models for estimating vancomycin clearance from creatinine clearance in Thai adult patients - Aim On Pradoo (2018)
© 2014 Faculty of Pharmaceutical Sciences, Chulalongkorn University. All rights reserved. This prospective study was performed to determine the best published model for estimating vancomycin clearance from creatinine clearance (CLcr) in Thai adult patients with CLcr greater than or equal to 30 ml/min. Data from 36 adult patients, who were given intravenous vancomycin were collected. Peak and trough concentrations of vancomycin at steady state were used to determine their vancomycin clearance (CLvanco) which was defined as their reference CLvanco (CLreference). The estimated CLvanco from each of the eight selected models was then compared with the CLreference. Mean error (ME) and root mean square error (RMSE) were examined to reflect performance of each model. In this analysis, the mean + SD of CLreference was 4.34 + 1.83 L/hr (CV = 42 %). The estimated CLvanco valued 4.21 + 1.39 L/hr from Birt model showed the least bias (ME -0.12 L/hr, P = 0.63 and RMSE 1.49 L/hr) while the revised Burton model and the Duchare model being the second and third best, respectively. Although wide variations in CLvanco among patients were observed, the results suggest that Birt model is more accurate in CLvanco prediction than the seven other models in this population. However, further studies with larger sample sizes are required to provide more definitive evidence.